Grading system for Hill-Sachs lesion and its association with Bankart lesion: a cross-sectional study - Rani Ahmad (BMC Musculoskeletal Disorders)
Abstract Background Bankart lesions and Hill-Sachs lesions can be detected in up to the majority of recurrent dislocations. This study aims to develop a grading system for Hill-Sachs lesions and assess its association with Bankart lesions. The proposed grading system, based on the dimensions of Hill-Sachs lesions, offers a standardized approach for classifying these defects, thereby facilitating the comparison of research findings across studies. Additionally, this study tends to estimate the highly significant association between Hill-Sachs lesions and the presence of Bankart lesions compared to previous studies. Methods A cross-sectional study, by procuring data from 94 patients, with shoulder dislocation and had been examined through MRI at the radiology department at King Abdul-Aziz University Hospital between 2019 and 2022. The sample was comprised of the patients who were diagnosed with either Hill-Sachs lesion or Bankart lesion, or concurrently with both of the lesions. Results The findings showed that the proposed grading system of Hill-Sachs had a significant association with the presence of Bankart lesions. Grade I in all dimensions, i.e., transverse diameter (P =.000), height (P =.005), and depth (P =.000), had a lower number of cases with Bankart lesions compared to Grade III, and the latter association was significant. Further, independent of the grading system, a statistically significant relationship was found between the width, diameter, and depth of Hill-Sachs lesion defects and the presence of Bankart lesions. Also, the presence of both lesions depicted a high risk for downsloping (P =.007). Conclusion The proposed grading system for Hill-Sachs lesions is a valid tool to assess the association between Bankart lesions and Hill-Sachs defects. Additionally, a significant relationship exists between Bankart lesion and Hill-Sachs lesions, along with their dimension, with a moderate correlation between maximum depth and volume of Hill-Sachs lesion with Bankart lesion, whereas a weak correlation between maximum transverse diameter and height with Bankart lesion.